PERANCANGAN AUDIO VISUAL PROMOSI DISTRO “MESIN HUJAN” PADANG - FADLI ELAKARDHO ELZA, Drs. Syafwandi, M.Sn, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Mesin hujan is a developing distro in Padang. Mesin hujan is locatied inJln. Damar 30B it has been established by 3 youth, Arif , Rizky and Fadli. They develop this factory since November 2012. Mesin hujan has philosophy meaning that mesin represent modern life and hujan represent sastra symbol. Hujan also can be the media to create romantism. From the romantism situation the owner of mesin hujan can create creative idea to make some poetry in order to put them in their cloth. In this occasion Mesin Hujan has their own characteristic in selling tshirt by putting some “puitis” word. For those reason Mesin Hujan need the media to extend the promotion , it need to refresh the media of promotion in shape of Audio Visual, in order the aim to streng then the promotion deliver to targetaudience.In process of creating it start from collection the data, observation, interview and documentation. Identification of problems is using SWOT analysis (Sterngth, Weakness, Opportunity, Threat) in order the problem of promoting Mesin Hujan can be found, analysis SWOT is using for evaluating and reevaluating a problem that have been decided before to minimize the risk that will be faced.The result of the design ia Audio Visual media that is packaged in DVDand MOV format to be uploaded to internet which is performing Audio Visual Mesin Hujan Padang. Audio Visual is using visualization about product tata ruang Mesin Hujan Padang and it is completed by music. The prime media of promotion is completing the supporting media such us, CD cover, Cd label, poster, sticker, pin, key chain, x-banner, member card.Keywords : Audio Visual, Mesin Hujan, Promotion